The Effectiveness of Using Luvlingua Learning Media to Enrich Students' Vocabulary on 'Names of Places' at SMAN 11 Medan - Sinaga, Seny Andryani; Soraya, Tengku Ratna (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2025)
This research aims to describe the effectiveness of using Luvlingua as a learning medium to enrich students’ vocabulary of place names at SMAN 11 Medan. The study addresses issues such as low vocabulary mastery, difficulty in identifying word gender, and lack of adequate learning media among XII IPA-2 students. Based on the pretest results, 36 students had not met the passing grade, with an average score of 45.56. This experimental study used a one-group pretest-posttest design and purposive sampling. The treatment was conducted over three sessions. In the first session, students were introduced to Luvlingua, which features images, audio, and quizzes. The second session focused on learning place-related vocabulary and using them with the verbs aller and être. In the third session, students practiced speaking and received direct feedback. The posttest results showed significant improvement, with scores ranging from 75 to 100 and an average of 89.03. The N-gain score reached 80%, indicating high effectiveness. It is concluded that Luvlingua is an effective medium for enriching the vocabulary of place names XII IPA-2 students at SMAN 11 Medan.